Oribatid mites (Acariformes: Sarcoptiformes) in Sub-Antarctic Islands and Antarctica: a track analysis - R. De los Ríos-Escalante, Patricio; Jara-Seguel, Pedro; O. Ahaotu, Emmanuel (Ukrainian Antarctic Journal, 2024)
Southern non-marine mites are widely distributed in the continents that developed out of the macrocontinent Gondwana, with similar groups found in Australia, New Zealand, Sub-Antarctic Islands, and southern South America. In the present study, we conducted a literature analysis of non-marine oribatid (moss) mite species (Acariformes: Sarcoptiformes) studies at the Sub-Antarctic Islands and Antarctic continent, an applied a track analysis. The purpose of the study is to identify sites potentially inhabited by ancestor species and understand the biogeographical patterns of their dispersion to new sites where current species have arisen through speciation processes. The results of the track analysis revealed the existence of species that inhabit three main zones: the first track includes South Georgia and the Sub-Antarctic Islands of the South Atlantic, the southern Indian Ocean and southern Australia and New Zealand. The second track includes South Georgia Island and the Antarctic Peninsula; and the third track includes South Georgia Island and the Falkland Islands. All these tracks intersect in South Georgia Island, suggesting that this island would be the zone from which the species reported spread to the other sites mentioned, colonizing Antarctica, the Falkland Islands, and probably southern South America.